ALIRAN TARIQATULLAH DI KOTA MEDAN, SUMATERA UTARA: TARIQATULLAH RELIGIOUS GROUP IN THE CITY OF MEDAN, NORTH SUMATERA - Abdul Malik MTT (Penamas, 2014)
This article discusses a religious group Tariqatullah, which has developed in the City of Medan, North Sumatera. It is based on a case study conducted by the author in 2013. Data collection methods include depth-interviews, participant observation, and desk study. The author found that this religious group puts more emphasis on zikr (remembrance of God) as a way to achieve self-purification, rather than on other Islamic rituals, such as obligatory salat (prayer), fasting in Ramadan, zakat (alms-paying), and hajj (pilgrimage to Mecca). The group tends to be exclusive so that most local residents do not aware their presence.While MUI (Islamic Scholars Council) of the City of Medan has considered the group as deviant, however, some of community leaders view that the members of the group are only misguided. Key Words: Tariqatullah, deviant sect, Medan. Tulisan ini mendiskusikan aliran Tariqatullah yang saat ini berkembang di Kota Medan, Sumatera Utara. Tulisan ini didasarkan pada penelitian yang dilakukan di tahun 2013. Penelitian ini menggunakan metode observasi partisipan, wawancara mendalam, dan studi dokumen. Penelitian ini menyimpulkan, bahwa aliran ini lebih menekankan kepada â€œzikirâ€ sebagai upaya pembersih diri, ketimbang ajaran salat, puasa, zakat, dan haji. Aliran terkesan sangat tertutup, sehingga hanya sedikit masyarakat yang tahu keberadaannya. Walaupun dianggap sesat oleh MUI Kota Medan, namun ada juga sebagian tokoh masyarakat mengatakan aliran ini bukan sesat tetapi salah jalan. Kata Kunci: Aliran Tariqatullah, aliran sesat, Medan.